Medsebojno doživljanje pri celostni obravnavi bolnika - Vegelj-Pirc, Marija (Obzornik zdravstvene nege, 1995)
The article describes the holistic concept of man from the point of view of logotherapy, and analyses the dynamics of the relationship between a patient and a nurse. Theoretical knowledge about the purpose of life, suffering and work is being illustrated with the cases of oncological patients. The need for the rehumanization of medicine is stressed.
Keywords: bolniki; Holistic health; komunikacija; logoterapija; medicinske sestre; Nurse-patient relations; odnosi; zdravstveno varstvo